Analisis Konseptual Pengantar Ilmu Hukum dan Tata Hukum Indonesia dalam Hukum Bisnis Syariah - Aghil Samudra Arya; M.Fadzla Ramandha Pane (Medan Resource Center, 2026)
This study aims to analyze the conceptual role of Introduction to Legal Science and the Indonesian Legal System in understanding the development of Islamic Business Law in Indonesia. The research employed a qualitative approach using a library research method with a conceptual analysis framework. Data were collected from primary legal sources, including statutory regulations, and secondary sources such as books, scholarly journals, and relevant legal literature. The findings indicate that Islamic Business Law has evolved from a normative concept of fiqh muamalah into an integral part of the Indonesian national legal system through legislative recognition, institutional development, and legal enforcement mechanisms. The study also reveals that the Introduction to Legal Science provides a theoretical foundation for understanding legal principles, functions, and objectives, while the Indonesian Legal System explains the legal position and institutional legitimacy of Islamic Business Law within the national legal framework. Furthermore, Islamic Business Law demonstrates adaptability to contemporary economic developments, particularly digital transactions, without abandoning fundamental Sharia principles. This study contributes a conceptual framework integrating legal theory and the Indonesian legal system to provide a more comprehensive understanding of Islamic Business Law in contemporary legal and economic contexts.